Circ_0084582 Facilitates Cell Growth, Migration, Invasion, and Angiopoiesis in Osteosarcoma via Mediating the miR-485-3p/JAG1 Axis - Gao, Peng; Zhao, Xincheng; Yu, Keying; Zhu, Ziqiang (Frontiers in Genetics, 2021)
Osteosarcoma (OS) is the most representative bone cancer, and circular RNAs (circRNAs) serve as pivotal regulators in the progression of OS. This research was designed to explore the role and functional mechanism of circ_0084582 in OS. Circ_0084582, microRNA-485-3p (miR-485-3p) and Jagged1 (JAG1) levels were measured by quantitative real-time polymerase chain reaction (qRT-PCR). Cell proliferation was examined via 3-(4, 5-dimethylthiazol-2-y1)-2, 5-diphenyl tetrazolium bromide (MTT) assay. Cell cycle progression was analyzed by flow cytometry. Wound healing assay and transwell assay were performed for evaluating cell migration and invasion. Angiopoiesis was assessed using tube formation assay. The protein detection was conducted using western blot. The target relation was identified by dual-luciferase reporter assay, RNA immunoprecipitation (RIP) assay and RNA pull-down assay. Xenograft experiment was applied for analyzing the effect of circ_0084582 on OS in vivo. Circ_0084582 was highly expressed in OS tissues and cells. Circ_0084582 knockdown reduced cell proliferation, cell cycle progression, migration, invasion and angiopoiesis of OS cells. JAG1 was upregulated in OS and its overexpression reversed the effects of circ_0084582 knockdown on OS cells. Circ_0084582 targeted miR-485-3p and miR-485-3p targeted JAG1, and circ_0084582 could affect the JAG1 level by sponging miR-485-3p. The function of circ_0084582 in the OS progression was also achieved by sponging miR-485-3p. Circ_0084582 knockdown decreased OS growth in vivo partly by the miR-485-3p-mediated JAG1 downregulation. These results indicated that circ_0084582 functioned as a tumorigenic factor in OS via the regulation of miR-485-3p/JAG1 axis.